About concept substitution in the philosophical and linguistic beliefs of Wilhelm von Humboldt and its influence on modern linguistics - Sergiy Popov (Вісник Харківського національного університету імені В. Н. Каразіна. Серія Філологія. Vìsnik Harkìvsʹkogo nacìonalʹnogo unìversitetu ìmenì V.N. Karazìna. Serìâ Fìlologìâ., 2023)
The article is devoted to exposing the logical fallacy of concept substitution in the philosophical and linguistic beliefs of Wilhelm von Humboldt and its influence on modern linguistics. After paying tribute to the famous scientist, it notes the well-known fact that in his famous 1820 lecture, Humboldt presented the ideas of the stage concept of language in such a way as to affirm the notion of root languages transitioning into incorporative ones, incorporative into agglutinative, and agglutinative into inflectional as the most perfect. It points out that Humboldt's assertion of such transitions was unanimously recognized by the linguistic community as erroneous. The article then gradually examines Humboldt's logically flawed statements, which can be seen as harbingers of the error this article focuses on: the contradiction between the scientist's claims that a people's spirit and language are identical, yet language depends on spirit, and that thinking not only depends on language but is determined by it. Next, the author discusses Humboldt's logical error, exposing which is the purpose of this article: the understanding of language as an independently existing entity, substituting the concept of a human-created communicative system with the concept of a human-created independently acting entity. It is suggested that Humboldt's logical mistake was to some extent caused by the prevailing ideology of idealistic Romanticism, which led him to make language a vivid, independent individuality. Furthermore, Humboldt made this error because of the superficial perception of the mobility of language as caused by its independence, while in fact such mobility is caused by the subconscious thinking of its speakers, which the scientist failed to grasp. Therefore, the article discusses the numerous instances where modern linguists continue to cite and comment positively on these flawed statements by Humboldt, and expresses the hope that this article will somewhat contribute to understanding the fallacy of the studied philosophical and linguistic beliefs of Wilhelm von Humboldt, which in turn will prevent their influence on modern linguistics.